Pengaturan Sanksi Kumulatif dalam Tindak Pidana Korupsi - I Made Sandi Cahyadi; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2020)
Corruption is a crime against social and economic rights of the community. Corruption has become an extraordinary crime or crime. Likewise, the eradication effort can no longer be done in the usual way, but must use extraordinary methods. Corruption is an evil act that can make the country a loss. In Indonesia, corruption has been widespread in society, its development continues to increase from year to year. This study aims to analyze the regulation of cumulative sanctions in corruption and analyze the judges' consideration in imposing criminal sanctions in place of fines as one of the cumulative sanctions in corruption. The research used was normative legal research using a statutory approach, conceptual approach, case approach which was then analyzed descriptively. Based on the results of the discussion it can be explained that the regulation of cumulative sanctions in corruption is regulated in article 2, article 6, article 8, article 9, article 10, article, 12, article 12B. Judge's consideration in giving a ruling is judicial consideration and seeing the legal facts revealed in the trial. So it can be concluded that the approach used by the judge in consideration of the decision is the balance theory, the theory of the art approach and intuition, the scientific approach theory, the experience approach theory and the ratio decidendi theory.